Microbiological assay for lomefloxacin in coated tablets - Gomes, Greici Cristiani [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Oxford University Press (OUP), 2006)
The validation of a microbiological assay, applying cylinder plate method for determination of the activity of lomefloxacin in coated tablets is described. Using a strain of Bacillus subtilis ATCC 9372 as the test organism, lomefloxacin was measured in concentrations ranging from 2.0 to 8.0 μg/mL. The method validation showed that it is linear (r= 0.9999), precise (relative standard deviation = 1.15%), and accurate (it measured the added quantities). The excipients did not interfere in the determination. It was concluded that the microbiological assay is satisfactory for quantitation of lomefloxacin in tablets.